SANS analysis of aqueous dispersions of Eu- and Gd-grafted nanodiamond particles. Issue 4 (2nd April 2020) - Tomchuk, Oleksandr V.; Ryukhtin, Vasyl; Ivankov, Oleksandr; Ya. Vul', Aleksandr; Aleksenskii, Aleksandr E.; Bulavin, Leonid A.; Aksenov, Victor L.; Avdeev, Mikhail V.
Abstract: The structure of detonation nanodiamond aqueous dispersions grafted by europium or gadolinium atoms was investigated by small-angle neutron scattering over a wide size scale from 1 to 3000 nm. Similar to the previous studies of nanodiamond suspensions, a strong association of the particle into developed aggregates was revealed. While the characteristic aggregate size depends on the modification of the dispersions and varies in a wide interval of 35–1500 nm, the fractal character of clusters of nanodiamond particles (packed in a specialized branched form with a fractal dimension of 2.4) remains unchanged independent of the cluster size. The effect of the aggregate size increase upon grafting is considered as a basis for the stability reduction mechanism at the microstructural level.